2004
DOI: 10.1177/039139880402700510
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Bridge to Heart Transplantation by Venoarterial ECMO and Transaortic Left Ventricular Venting

Abstract: We report a case in which life support for cardiogenic shock was achieved by a nonpulsatile venoarterial bypass, and left ventricular decompression was obtained by a catheter placed percutaneously through the aortic valve into the left ventricle. The blood drained from the left ventricle was pumped into the femoral artery. The normalization of left heart filling pressures allowed the resolution of pulmonary edema, and the patient underwent a successful heart transplantation following 7 days of mechanical cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 18 publications
0
35
0
3
Order By: Relevance
“…LV unloading was successfully achieved and pulmonary oedema was finally solved. Heart transplantation was performed after 7 days of ECMO support …”
Section: Percutaneous Venting Of the Left Ventriclementioning
confidence: 99%
“…LV unloading was successfully achieved and pulmonary oedema was finally solved. Heart transplantation was performed after 7 days of ECMO support …”
Section: Percutaneous Venting Of the Left Ventriclementioning
confidence: 99%
“…The combination of extensive LV or pulmonary vascular thrombosis with acute respiratory distress syndrome would limit options for recovery, heart transplant, or transition to a long-term VAD systems. [9][10][11] Lastly, the extent of pulmonary vascular injury may be underappreciated because the pulmonary vasculature is relatively underperfused and the majority of the cardiac output is diverted away from the lungs during VA ECMO support. A chest x-ray on VA ECMO may appear fairly normal in the setting of diminished pulmonary flow only to reveal the deleterious effects of the acute pulmonary venous hypertension once pulmonary arterial flow is restored.…”
mentioning
confidence: 99%
“…Multiple techniques to achieve decompression by creating an unrestrictive interatrial communication, including balloon atrial septostomy (12), transseptal puncture and balloon dilation of the atrial septum (13)(14)(15), and puncture and stenting of the atrial septum (16), have been reported. Additional reports have described introduction of a vascular sheath across the atrial septum (17)(18)(19) and retrograde placement of a drainage catheter into the left ventricle through the aortic valve (20). In our patient, attempts at crossing the interatrial septum to perform a balloon atrial septostomy were unsuccessful, and a full sternotomy was required to allow direct cannulation through the LA.…”
Section: Discussionmentioning
confidence: 80%